2008
DOI: 10.1007/s11251-008-9052-y
|View full text |Cite
|
Sign up to set email alerts
|

Does musical training improve school performance?

Abstract: In a retrospective study, we compared school performance of 53 children practicing music (group 1) with 67 controls not practicing music (group 2). Overall average marks as well as average marks of all school subjects except sports were significantly higher in children who do (group 1) than in those who do not practice music (group 2). In a multiple regression analysis, musical training, parent's income, and educational level (grades) correlated significantly with overall average marks. A slight decrease of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 23 publications
(26 reference statements)
10
40
1
1
Order By: Relevance
“…Similarly, Forgeard et al (2008) reported that music discrimination skill correlated with phonological processing ability in a group of dyslexic and typically-developing children. In line with these studies, Wetter, Koerner, and Schwaninger (2009) reported a positive relationship between engagement in musical activities and overall academic attainment.…”
Section: Correlational Evidencesupporting
confidence: 74%
“…Similarly, Forgeard et al (2008) reported that music discrimination skill correlated with phonological processing ability in a group of dyslexic and typically-developing children. In line with these studies, Wetter, Koerner, and Schwaninger (2009) reported a positive relationship between engagement in musical activities and overall academic attainment.…”
Section: Correlational Evidencesupporting
confidence: 74%
“…Conscientiousness (self‐discipline, organisation and achievement‐orientation) and openness‐to‐experience (the tendency to have an active imagination, to prefer change and variety over routine, to be intellectually curious) were suggested as two examples of capacities that music training promoted. A greater influence from EC music practice on overall school mark was seen in Grade 6 students (age 12) who had been practising for longer than Grade 3 students (age 9; Wetter et al ., ). Showing a similar dose–response relationship, the effect size of the impact upon the overall Ohio Proficiency Test score was greater in the Grade 9 students (aged 15 years) than in Grade 4 (age 9; Fitzpatrick, ).…”
Section: Evidence For Dual Step Transfer: Non‐sport Ec (Nsec) Activitiesmentioning
confidence: 97%
“…The wisdom of the ages encapsulated in the concept of mens sana in corpore sano (healthy mind in a healthy body) has received considerable attention in the research literature, and assumes a causal relationship leading from the healthy body to the healthy mind. Significantly, sport and non-sport EC activities have been shown to provide low to moderate benefit to academic results in terms of effect size (Camp, 1990;Shephard, 1997;Sallis et al, 1999;Schellenburg, 2004Schellenburg, , 2006Wetter et al, 2009;Bradley et al, 2013). However, despite the proliferation of studies, until recently little conceptualisation existed over how this benefit may be caused and the actual benefits of participating in school sport and non-sport extracurricular activities (Shulruf, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this continues to happen in spite of research that clearly indicates how allowing students' opportunities to participate in arts programs has been shown to boost academic achievement (Bamford, 2006;Catterall, Chapleau & Iwanaga, 1999;Wetter, Koerner, Schwaninger, 2009;Vaughan, Harris & Caldwell, 2011) particularly in relation to the areas of Government focus and funding -literacy and numeracy. Music instruction in particular, has been shown to significantly increase spatial-temporal reasoning skills (Hetland, 2001), encourage mathematical reasoning (Vaughan, 2001), improve numeracy (Hunter, 2005;Spillane, 2009) and mathematics (Bamford, 2006;Catteral, Chapleau & Iwanaga, 1999;Hunter, 2005;Uptis & Smithrim, 2003;Vaughan, Harris & Caldwell, 2011).…”
Section: Value Of the Arts In Educationmentioning
confidence: 99%